Analisis Persepsi Masyarakat terhadap Adopsi QRIS sebagai Instrumen Akselerasi Ekonomi Digital di Kota Denpasar - I Komang Trisna Eka Putra; Ni Nyoman Rika Lestari; Aditya Manggala, RS; I Wayan Sugiartana (Universitas Tabanan, 2026)
This research sought to examine the evolution of financial behavior in the digital age, focusing on the impact of digital banking and financial literacy on the saving choices of working-age populations. The study challenge centered on the decreased propensity to save despite the rapid advancement of digital financial services. The research used a conceptual framework bolstered by an examination of pertinent empirical evidence to elucidate the correlation between factors. The findings demonstrated that digital banking facilitated accessibility, transaction efficiency, and service adaptability, which motivated consumers to improve their saving choices. Financial literacy significantly influenced the acquisition of information, awareness, and the capacity to handle personal funds judiciously and methodically. The integration of digital banking and financial literacy significantly enhanced saving choices among persons of productive age. The use of digital financial technology, along with sufficient financial awareness, facilitated more efficient and sustainable financial practices. This research provided actionable insights for financial institutions and policymakers in developing measures to improve saving behavior within the community.